Ice‐margin retreat and grounding‐zone dynamics during initial deglaciation of the Storfjordrenna Ice Stream, western Barents Sea - Shackleton, Calvin; Winsborrow, Monica; Andreassen, Karin; Lucchi, Renata Giulia; Bjarnadóttir, Lilja Rún (Boreas, 2019)
Processes occurring at the grounding zone of marine terminating ice streams are crucial to marginal stability, influencing ice discharge over the grounding‐line, and thereby regulating ice‐sheet mass balance. We present new marine geophysical data sets over a ~30×40 km area from a former ice‐stream grounding zone in Storfjordrenna, a large cross‐shelf trough in the western Barents Sea, south of Svalbard. Mapped ice‐marginal landforms on the outer shelf include a large accumulation of grounding‐zone deposits and a diverse population of iceberg ploughmarks. Published minimum ages of deglaciation in this region indicate that the deposits relate to the deglaciation of the Late Weichselian Storfjordrenna Ice Stream, a major outlet of the Barents Sea–Svalbard Ice Sheet. Sea‐floor geomorphology records initial ice‐stream retreat from the continental shelf break, and subsequent stabilization of the ice margin in outer‐Storfjordrenna. Clustering of distinct iceberg ploughmark sets suggests locally diverse controls on iceberg calving, producing multi‐keeled, tabular icebergs at the southern sector of the former ice margin, and deep‐drafted, single‐keeled icebergs in the northern sector. Retreat of the palaeo‐ice stream from the continental shelf break was characterized by ice‐margin break‐up via large calving events, evidenced by intensive iceberg scouring on the outer shelf. The retreating ice margin stabilized in outer‐Storfjordrenna, where the southern tip of Spitsbergen and underlying bedrock ridges provide lateral and basal pinning points. Ice‐proximal fans on the western flank of the grounding‐zone deposits document subglacial meltwater conduit and meltwater plume activity at the ice margin during deglaciation. Along the length of the former ice margin, key environmental parameters probably impacted ice‐margin stability and grounding‐zone deposition, and should be taken into consideration when reconstructing recent changes or predicting future changes to the margins of modern ice streams.